Analysis of Work-Life Balance and Job Satisfaction in Improving Employee Performance Mediated by Work Motivation - Nawawi, Nawawi; Wahyudi, Wahyudi; Abdurrohman, Abdurrohman (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2025)
The complexity of problems in the work environment demands attention to work-life balance (WLB) and job satisfaction as key determinants of employee performance, with work motivation acting as a mediating variable that strengthens the causal relationship between working conditions and individual productivity. This study aims to examine the influence of WLB and job satisfaction on employee performance, focusing on the mediating role of work motivation within a government context. Using a quantitative approach, primary data were collected through questionnaires distributed directly to 70 employees of the Serang District Ministry of Religion Office, and the relationships between variables were tested using PLS-SEM version 4.0. The empirical findings reveal that WLB neither directly nor indirectly influences employee performance. Conversely, job satisfaction significantly affects work motivation, which positively contributes to improving employee performance. Furthermore, work motivation mediates the relationship between job satisfaction and performance, but it does not serve as a mediating factor between WLB and performance. These findings underscore the importance of implementing human resource management strategies centered on performance enhancement to foster a more motivated and productive workforce, which, in turn, can support the efficiency of public sector services and contribute to broader economic growth